Cystic apocrine hyperplasia is the most common finding in MRI detected breast lesions. Issue 2 (22nd October 2013) - Ginter, Paula S; Winant, Abbey J; Hoda, Syed A
Abstract : MRI of the breast is an increasingly employed modality for breast imaging due to its relatively high sensitivity for the detection of breast carcinoma. Cumulative data indicate that MRI of the breast has relatively higher sensitivity, but lower specificity than mammography. However, data regarding the diagnostic yield for particular types of breast lesions detected via breast MRI remain scant. Over a 3.5-year period, we evaluated histological findings of 192 needle core biopsies of MRI detected breast lesions. In this series, the positive predictive value of MRI detected lesions for breast carcinoma was 20%. Invasive carcinoma was diagnosed in 16/192 (8%) and in situ carcinoma in 22/192 (11%). The most commonly detected histological finding was cystic apocrine hyperplasia (19%), a benign entity.